2013
DOI: 10.1109/tnsre.2012.2228674
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of TMS Induced Artifacts in EEG Using Principal Component Analysis

Abstract: Co-registration of transcranial magnetic stimulation (TMS) and electroencephalography (EEG) is a new, promising method for assessing cortical excitability and connectivity. Using this technique, a TMS evoked potential (TEP) can be induced and registered with the EEG. However, the TEP contains an early, short lasting artifact due to the magnetic pulse, and a second artifact, which depends on the location of stimulation and can last up to 40 ms. Different causes for this second artifact have been suggested in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 23 publications
0
59
0
Order By: Relevance
“…Furthermore, subthreshold TMS pulses induced larger N100 than sham TMS despite the fact that sham TMS had louder sound. Previous studies also showed that earplug or other sound-attenuating methods sharply reduced TMS-evoked N100 (Ter Braack et al 2015), and the TMS-evoked N100 and P200 were also presented when subject was completely deaf (Ter Braack et al 2013). …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, subthreshold TMS pulses induced larger N100 than sham TMS despite the fact that sham TMS had louder sound. Previous studies also showed that earplug or other sound-attenuating methods sharply reduced TMS-evoked N100 (Ter Braack et al 2015), and the TMS-evoked N100 and P200 were also presented when subject was completely deaf (Ter Braack et al 2013). …”
Section: Discussionmentioning
confidence: 97%
“…2b) when single-pulse TMS was delivered over the superior parietal lobule. Also, TMS-evoked N100 was obtained with single vertex stimulation after removing auditory confounds (Ter Braack et al 2013). However, those N100 evoked by single-pulse TMS over different brain areas were demonstrated separately, and hence, there was no direct comparison between those N100s.…”
Section: Discussionmentioning
confidence: 99%
“…The P60 component is believed to reflect somatosensory return (Paus et al, 2001), and the N100 has been associated with the activation of GABA-B receptors (Bonnard et al, 2009; Nikulin et al, 2003; Premoli et al, 2014). The P60, N100 and P180 components are also thought to be contaminated with an auditory evoked potential originated from the TMS pulse click (ter Braack et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Another technique implemented in the comparison was PCA. PCA [25][26][27] is a well-established multivariate data technique which finds the direction in the data with most variation. It is expected that the direction with most variation contains the noise signals, because of the large amplitude difference between noise and EEG signals.…”
Section: Benchmark Methodsmentioning
confidence: 99%
“…One of the common approaches is the adaptive filtering (AF) architecture which has been used for interference cancellation of EEG [15][16][17][18][19] and wavelet [20][21][22][23]. In this context, principal component analysis (PCA) [24][25][26][27] and independent component analysis (ICA) [23,[28][29][30][31][32][33][34] have become popular for analysing biomedical data (e.g., EEG and EMG). One of the main advantages of these approaches relates to their applicability to multisensory observations of mixed signals.…”
Section: Introductionmentioning
confidence: 99%